A scaling relation of vortex-induced rectification effects in a superconducting thin-film heterostructure - Yusuke Kobayashi; Junichi Shiogai; Tsutomu Nojima; Jobu Matsuno (Communications Physics)
Abstract Supercurrent rectification, nonreciprocal response of superconducting properties sensitive to the polarity of bias and magnetic field, has attracted growing interest as an ideal diode. While the superconducting rectification effect is a consequence of the asymmetric vortex pinning, the mechanisms to develop its asymmetric potentials have been a subject of ongoing debate, mainly focusing on microscopic breaking of spatial inversion symmetry and macroscopic imbalance of the sample structure. Here, we report on comparative study of the superconducting diode effect and nonreciprocal resistance in a superconducting Fe(Se,Te)/FeTe heterostructure. In normal state, we observe finite nonreciprocal resistance as a hallmark of the spin-orbit interaction with structural inversion asymmetry. In the superconducting state, we find that the strongly enhanced nonreciprocal coefficient in transition regime is directly coupled to the superconducting diode efficiency through a universal scaling law, indicating the role of spin-momentum-locked state on the asymmetric pinning potential. Our findings, providing a unified picture of the superconducting rectification, pave the way for functionalizing superconducting diode devices.